Kesesuaian Wisata Selam dan Snorkeling di Pulau Makasar, Kota Baubau - La Ode Abdul Rajab Nadia; Dedy Oetama; Amadhan Takwir; Muhammad Fajar Purnama; Muhammad Trial F. Erawan; Laode Muhamad Hazairin Nadia (Kainawa: Jurnal Pembangunan dan Budaya, 2020)
Makasar Island, Baubau City has a varied coastal and marine resource potential, among others, coral reef ecosystem. The coral reef ecosystem has potential to development of marine tourism (diving and snorkeling). The objective of the research is to find out the condition and potential of the coral reef ecosystem, to study its suitability for marine tourism objects of diving and snorkeling, and to study the carrying capacities for the activities in the area of coral reef ecosystem. The analyzing equipment used to measure the marine tourism suitability is suitability matrix of diving and snorkeling, the supporting equipment with the total area used per number of tourists. The result of suitability analysis showed 5 potential areas for diving and snorkeling activities. Category suitability for snorkeling and diving are suitable (S2). The carrying capacity of the Makasar island area is suitable (S2) for snorkeling and diving tours.